The Dualism of Economic Systems and Its Role in Development of Economies (Baltic Journal of Real Estate Economics and Construction Management, 2013)
The role of economic dualism in the evolution of economic systems are tackled in the article. It shows that economic systems have the properties similar in their manifestation to dualism.